Characterization, Conservation, and Breeding of Winter Squash (Cucurbita moschata Duchesne): Case Study of the Collection Maintained at the Federal University of Viçosa Vegetable Germplasm Bank - Derly José Henriques da Silva; Ronaldo Silva Gomes; Ronaldo Machado Júnior; Cleverson Freitas de Almeida; Rebeca Lourenço de Oliveira; Dalcirlei Pinheiro Albuquerque; Santina Rodrigues Santana (Plants)
Winter squash (Cucurbita moschata Duchesne.) is a vegetable of high socioeconomic importance owing to the nutritional quality of its fruits, seeds, and seed oil. This study aims to review the main aspects related to the characterization, conservation, and breeding of C. moschata, emphasizing the studies with C. moschata accessions maintained by the Vegetable Germplasm Bank of the Federal University of Viçosa (BGH-UFV). Studies on C. moschata germplasm have reported high variability, particularly in Brazil. Currently, Brazil maintains six Cucurbita germplasm collections, kept in research and teaching institutions. The BGH-UFV collection, one of the largest in the country, contains approximately 350 accessions of C. moschata, mostly landraces collected from all over Brazil. Studies characterizing this germplasm have identified promising genotypes as sources of alleles for increasing the carotenoid content in the fruit pulp and oleic acid content in the seed oil. As part of a breeding program to increase seed oil productivity and improve the oil profile, studies with the BGH-UFV germplasm have identified C. moschata genotypes with seed oil productivity of up to 0.27 t ha−1 and accessions producing oil with high oleic acid content (21 to 28%). The genetic breeding program of C. moschata conducted at the UFV has prioritized the development of compact growth habit genotypes to reduce plant spacing and increase seed and oil productivity. The works involving the collection of C. moschata maintained by the BGH-UFV corroborates the importance of this germplasm as a source of alleles for improving seed oil productivity and the oil profile.